Unit root tests of the current account balance: implications for international capital mobility - Erich Gundlach; Stefan Sinn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
This paper assesses the extent of international capital mobility in a time series context. It explores the possibility that the current account balance of different OECD-countries contains a unit root. It is shown that if the ratio of the current account balance to GDP is found to be integrated of the order of one, the country is likely to be part of the world capital market. The results for the whole period 1950-1988 indicate that the current account balance of at least Germany, Japan, and the United States contains a unit root. Considering the subperiods before and after 1972 it is shown that international capital mobility increased after the breakdown of the Bretton Woods System.
Keywords: F21; F32; 330; International capital mobility; current account adjustment; unit root tests